Studies of L‐phenylalanine production by immobilised aminoacylase in stabilized calcium alginate beads - Lee, Kong H.; Lee, Pat M.; Siaw, Yew S. (Society of Chemical Industry, 1992)
Aminoacylase I (EC 3.5. 1.14) was immobilised by entrapment in uncoated calcium alginate beads and calcium alginate beads coated with chitosan, polyethyleneimine and polyethyleneimine‐glutaraldehyde for the production of L‐phenylalanine by the hydrolysis of a racemic mixture of N‐acetyl‐DL‐phenylalanine. The operational stability, thermal stability, effects of pH and temperature and kinetic constants, Km and Vmax values of free and immobilised enzymes were studied. Scanning electron micrographs revealed differences in the structures of the surfaces of coated and uncoated beads. Chitosan‐coated calcium alginate beads was found to be the best among the immobilised systems studied. The activity and the optimum temperature of immobilised aminoacylase were higher than those of the free enzyme. In addition, the beads showed stable activity under operational conditions. The immobilised aminoacylase lost about 20% of its initial activity after ten cycles of reuse. Polyethyleneimine and polyethyleneimine‐glutaraldehyde treatments were also found to enhance the operational stability of the enzyme but its activity was greatly reduced. Copyright © 1992 Society of Chemical Industry